Citizenship Catechesis Initiation for Mainstreaming Political Engagement Among the Z Faithful Digital Generation - Kristhalia Dessindi; Mutiara Andalas (P3TK, Sanata Dharma University, 2022)
Catholic Bishop Conference through the Catechetical Commission Catholic to youth to involve in political issues and to become political leaders has become an embryonic momentum for ‘citizenship catechesis’. How does social activism among Catholic youth at St. Anthony of Padua Parish in Kotabaru Yogyakarta become the embryo of the birth of citizenship catechesis? The two authors conducted qualitative research with a naturalistic descriptive design through participative observation, literature review and semi-structured interviews to collect data. The Catholic youth in St. Anthony of Padua Parish in Kotabaru Yogyakarta, who belong to the Z generation and are actively involved in social activism, is the leading research informant. Citizenship catechesis embryo grows organically through social activism, such as Interfaith Dialogue and Sega Mubeng. Ahead of the 2024 presidential election, parishes need urgently to initiate citizenship catechesis with activities that allow the faithful Z generation to borrow Pope Francis’ terminology, ‘to be involved, not just observers, even spectators.’